2021
DOI: 10.3390/pathogens10070912
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Immune Modulators in the Secretome of the Equine Tapeworm Anoplocephala perfoliata

Abstract: Anoplocephala perfoliata is a neglected gastro-intestinal tapeworm, commonly infecting horses worldwide. Molecular investigation of A. perfoliata is hampered by a lack of tools to better understand the host–parasite interface. This interface is likely influenced by parasite derived immune modulators released in the secretome as free proteins or components of extracellular vesicles (EVs). Therefore, adult RNA was sequenced and de novo assembled to generate the first A. perfoliata transcriptome. In addition, exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 157 publications
(214 reference statements)
3
32
1
Order By: Relevance
“…Similarly, H. polygyrus ESPs were shown to exert antimicrobial activity against several Gram-negative and Gram-positive bacteria, including E. coli, Salmonella enterica serovar Typhimurium, Enterococcus faecium, and S. aureus [33]. In a recent proteomics analysis of A. suum ESPs, putative AMPs were localised to the EV-rich fraction [31] Trends Trends in in Parasitology Parasitology [31]; Hp, Heligmosomoides polygyrus [48]; Nb, Nippostrongylus brasiliensis [71]; Tc, Teladorsagia circumcincta [23,72]; Tm, Trichuris muris [72]; Fh, Fasciola hepatica [34,37,64]; Ap, Anoplocephala perfoliata [35]; Ta, Taenia asiatica [73]; Hd, Hymenolepis diminuta [74].…”
Section: Trends Trends In In Parasitology Parasitologymentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, H. polygyrus ESPs were shown to exert antimicrobial activity against several Gram-negative and Gram-positive bacteria, including E. coli, Salmonella enterica serovar Typhimurium, Enterococcus faecium, and S. aureus [33]. In a recent proteomics analysis of A. suum ESPs, putative AMPs were localised to the EV-rich fraction [31] Trends Trends in in Parasitology Parasitology [31]; Hp, Heligmosomoides polygyrus [48]; Nb, Nippostrongylus brasiliensis [71]; Tc, Teladorsagia circumcincta [23,72]; Tm, Trichuris muris [72]; Fh, Fasciola hepatica [34,37,64]; Ap, Anoplocephala perfoliata [35]; Ta, Taenia asiatica [73]; Hd, Hymenolepis diminuta [74].…”
Section: Trends Trends In In Parasitology Parasitologymentioning
confidence: 99%
“…Secretion of exosome-like particles has been ascertained in species of nematodes [23], trematodes [34], and cestodes [35], and confirmed using transmission electron microscopy (TEM) and/or nanoparticle tracking analysis (NTA). Exosome formation involves fusion of late endosomes with the plasma membrane and, as such, exosome-like particles are enriched with proteins of the endosomal sorting complexes required for transport (ESCRT) pathway, for instance, Rabs [36], Vps4 [36], Tyro3, Axl, and Mer (TAM)-binding protein, and TSG101 [37].…”
Section: Trends Trends In In Parasitology Parasitologymentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier immunoblotting studies have demonstrated that the antibody response to A. perfoliata E/S proteins of 12 and 13 kDa in size correlate with parasite infection intensity, but the identity of these proteins have remained unknown ( 12 , 13 , 15 ). A recent in-depth RNA sequencing study on this tapeworm generated the first transcriptome for A. perfoliata at its adult stage to support the identification of over 800 E/S proteins produced by this species ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…As such, the study provides an initial basis for understanding the immunological and pathological effects of this infection in humans. Next, Wititkornkul et al examine the immunomodulatory potential of extracellular vesicles (EVs) released by the equine tapeworm Anoplocephala perfoliata [ 12 ]. EVs have emerged as novel vehicles for transfer of helminth-derived molecules to host cells, and, by describing the cargo of A. perfoliata EVs, this paper uncovers potential mechanisms of parasite-to-host communication during infection.…”
mentioning
confidence: 99%